Fundamental of agricultural economic / by A. N. Sadhu and Amarjit Singh - Sadhu, A. N.; Singh, Amarjit (Bombay, 1985)
The second edition of the book is a revised and enlarged version of the first edition. Overwhelming reception and acceptability of the first edition has greatly encouraged us and we have made yet another modest attempt to meet the additional requirements of our readers by adding three very important and useful chapters in this edition. viz., Risk and Uncertainty in Agriculture, Supply Behaviour in Agriculture, and Transformation of Traditional Agriculture.
Keywords: IndiaAgriculture - Economic aspects